Os impactos da pandemia do Covid-19 em empreendedores do setor de eventos na cidade de João Pessoa/PB - Silva, Alexandra Rodrigues da (2022)
The research aimed to understand how entrepreneurs in the event sector in the city of João Pessoa/PB are dealing with the difficulties of the pandemic in the entertainment field, and how the dysfunctions of bureaucracy interfere with its functioning. For this study, theories on entrepreneurship and bureaucracy are covered and, as for the method, a qualitative approach was followed, and data was gathered accessing normative documents and performing semi-structured interviews with six (6) entrepreneurs of the field, transcribing and submitting the data to content analysis. Results indicated positive and negative impacts on a professional and personal level, regarding financial losses and also situations that affect the interviewees' life quality such as well-being and their emotions. Regarding bureaucratic issues, it was evident that the field had strong losses when following the measures proposed by the Government, as well as an impasse caused by the lack of aid aimed at the sector. Strategies adopted by the interviewees mainly involved reducing the values of the services provided, investing in social networks and creating new businesses as a source of income. In conclusion, despite minimal positive points, the greatest impact was of negative and financial kind, where entrepreneurs had to, out of necessity, devise ways to remain active.